2012
DOI: 10.1002/ijc.27434
|View full text |Cite
|
Sign up to set email alerts
|

Toenail trace element status and risk of Barrett's oesophagus and oesophageal adenocarcinoma: Results from the FINBAR study

Abstract: Trace elements have been cited as both inhibitory and causative agents of cancer but importantly exposure to them is potentially modifiable. This study aimed to examine toenail trace element status and risk of Barrett’s oesophagus (BO) and oesophageal adenocarcinoma (OAC). Toenail clippings from each hallux were obtained from 638 participants of the FINBAR study (Factors Influencing the Barrett’s Adenocarcinoma Relationship) comprising 221 healthy controls, 98 reflux oesophagitis, 182 BO and 137 OAC cases. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
18
3
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 42 publications
6
18
3
1
Order By: Relevance
“…Few other studies have measured chromium in toenails. The concentration of chromium in our study (0.71 μ g/g) was more than that reported in the FINBAR study conducted in Ireland (0.55 μ g/g) . Surprisingly, we also found an inverse association between toenail chromium concentration and risk of ESCC.…”
Section: Discussioncontrasting
confidence: 81%
See 1 more Smart Citation
“…Few other studies have measured chromium in toenails. The concentration of chromium in our study (0.71 μ g/g) was more than that reported in the FINBAR study conducted in Ireland (0.55 μ g/g) . Surprisingly, we also found an inverse association between toenail chromium concentration and risk of ESCC.…”
Section: Discussioncontrasting
confidence: 81%
“…We caution that the observed association is based on small case numbers. Also of note, the mean concentration of mercury among controls in this study was very low (0.04 ± 0.05 μ g/g) compared to those reported in the Nurse's Health Study (0.33 ± 0.63 μ g/g) and the Health Professionals Follow‐up Study (excluding dentists) (0.44 ± 0.47 μ g/g) in the US and the FINBAR case‐control study (0.11 ± 0.23 μ g/g) in Ireland .…”
Section: Discussioncontrasting
confidence: 70%
“…Quantification of elements in human finger- and toenails is an established biomarker for numerous essential and non-essential elements with and without known biological functions (53). Nails have been used previously as a biomarker for exposure to Hg (38, 5457), Mn (58), Se (57) and Zn (59, 60). Fewer studies have used nails as biomarkers of Cd and Pb, and for Pb have observed correlations with blood Pb concentrations, and with exposure (38).…”
Section: Discussionmentioning
confidence: 99%
“…Two case-control studies from Australia [28•] and Ireland [33] reported a 15-20% increased risk associated with selenium intake. However, results differed when toenail selenium concentrations were examined; the Irish case-control study found no association [39], and a Dutch case-cohort study reported a 24% decreased risk [40]. In a cohort study of BE patients that examined EA-related outcomes, EA risk was increased 40% in association with higher serum selenium concentrations [41].…”
Section: Antioxidants and Other Vitamins/mineralsmentioning
confidence: 99%
“…In contrast, three more recent case-control studies, conducted in Australia [28•], Ireland [33], and the U.S. [26••], found little or no association between selenium intake and BE. Toenail selenium levels were associated with modest 11% risk reductions in the Irish case-control study [39] and, among women only, in a Dutch case-cohort study [43]. …”
Section: Antioxidants and Other Vitamins/mineralsmentioning
confidence: 99%